Estimation of the Seroconversion Duration of HIV-1 Antibodies in Individuals With Recent Infection in China - Kong, Wen-Hua; Liu, Pan; Tang, Li; Zhu, Ze-Rong; Xiao, Peng; Zhan, Jian-Bo; Wang, Xia; Zhou, Wang; Liu, Man-Qing (Frontiers in Microbiology, 2019)
Identification of recent HIV-1 infection is clinically important for effective treatment and prevention of transmission. However, the window period for seroconversion with respect to various HIV-1 antibodies is not well characterized. In addition, the routine HIV testing algorithms are not particularly appropriate for identification of recent HIV-1 infection. In this study, we enrolled individuals who showed seroconversion from negative Western blot (WB) or indeterminate WB results and analyzed the window periods for appearance of HIV-1 antibodies. A total of 10,934 individuals with suspected HIV infection were tested by Wuhan CDC between 2012 and 2017; of these, 40 individuals with initial negative WB and 102 individuals with initial indeterminate WB who showed positive WB results within 100 days were included in the analysis. The mean time for seroconversion was 43.90 (95% confidence interval [CI]: 37.30–50.50) days and 42.15 (95% CI: 37.99–46.30) days, respectively. The time duration for p31 seroconversion among people with negative WB and indeterminate WB was 58.11 (95% CI, 44.30–71.92) days and 51.91 (95% CI, 44.55–59.28) days, respectively, both of which were significantly longer (p = 0.0169) than those in people without p31 seroconversion. Similar difference was observed with respect to p66 seroconversion, with window time of 53.53 (95% CI, 43.54–63.52) days and 47.87 (95% CI, 43.16–52.57) days among people with negative WB and indeterminate WB, respectively. These data suggest that HIV-1 antibody p66, like p31, may serve as a potential serological marker for distinguishing Fiebig stage V and stage VI at day 70 post-infection.